2016
DOI: 10.2134/agronj2015.0198
|View full text |Cite
|
Sign up to set email alerts
|

Forage Attributes and Animal Performance from Native Grass Inter‐Seeded with Red Clover

Abstract: Native warm‐season grasses (NWSG) could provide desirable complementary summer forage for tall fescue [TF; Schedonorus arundinaceus (Schreb.) Dumort.] systems, especially for reproductive animals that may be disproportionately affected by TF toxicosis. Inter‐seeding legumes into pastures is a common practice but has received only limited attention for NWSG. Switchgrass (SG; Panicum virgatum L.) and a big bluestem (BB; Andropogon gerardii Vitman) indiangrass (IG; Sorghastrum nutans Nash) blend (BB/IG), each wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 33 publications
(53 reference statements)
6
44
1
Order By: Relevance
“…Keyser et al (2016) reported little effect of overseeding red clover into NWSG on forage mass, CP, neutral detergent fiber, or animal performance, likely due to low levels of clover after establishment. The study concluded that alternative legume options for overseeding NWSG systems should be explored.…”
Section: Resultsmentioning
confidence: 99%
“…Keyser et al (2016) reported little effect of overseeding red clover into NWSG on forage mass, CP, neutral detergent fiber, or animal performance, likely due to low levels of clover after establishment. The study concluded that alternative legume options for overseeding NWSG systems should be explored.…”
Section: Resultsmentioning
confidence: 99%
“…For the perennial forages, a 10-yr production horizon with no grazing in the establishment year was assumed, which is typical for this region (Boyer, Tyler, Roberts, English, & Larson, 2012Lowe et al, 2015;Zhou, Boyer, Larson, & Lieb, 2014). Total establishment and production costs of native warm-season grasses were calculated following previous studies (Boyer, Griffith, Roberts, Savoy, & Leib, 2014;Keyser et al, 2016;Lowe et al, 2015Lowe et al, , 2016McFarlane, Boyer, & Mulliniks, 2018). Establishment costs, which included seed, fertilizer, herbicide, machinery, and labor, were annualized over the pasture production life using a discount rate of 5.5% (Boyer et al, 2012Lowe et al, 2015;McFarlane et al, 2018;Zhou et al, 2014).…”
Section: Budgetingmentioning
confidence: 99%
“…These net returns to grazing ranged from a low of $244 to $852 ha −1 , depending on WSG species and grazing management. Similarly, animal performance and economics of grazing bred heifers on WSG have proven favorable with cost of gain as low as $0.14 kg −1 for switchgrass ( Panicum virgatum L.; SG) pasture and $0.18 kg −1 when a combination of big bluestem ( Andropogon gerardi Vitman) and indiangrass ( Sorghastrum nutans L.; BI) was grazed (Keyser et al., ). Furthermore, costs for dairy heifers grazing SG and a BI blend were $0.38 and $0.65 head −1 d −1 , which are lower than the $1.89 head −1 d −1 that was estimated for using harvested commodity feeds (Lowe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The production of a legume and warmseason grass mixture might also increase farmer flexibility because the legume crop can be harvested and used as highquality animal feed (Bow et al, 2008). Field evaluations of mixtures of legumes and warm-season grasses for forage production have sometimes shown promising results (Ashworth et al, 2015), but it has also proved difficult to establish (Keyser et al, 2016) or maintain productivity (Biligetu et al, 2014) of these mixtures. Field evaluations of mixtures of legumes and warm-season grasses for forage production have sometimes shown promising results (Ashworth et al, 2015), but it has also proved difficult to establish (Keyser et al, 2016) or maintain productivity (Biligetu et al, 2014) of these mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The agronomic and environmental benefits of legume and cool-season grass mixtures in pasture systems have long been appreciated (Rochon and Doyle, 2004). Field evaluations of mixtures of legumes and warm-season grasses for forage production have sometimes shown promising results (Ashworth et al, 2015), but it has also proved difficult to establish (Keyser et al, 2016) or maintain productivity (Biligetu et al, 2014) of these mixtures. Several legume species have been found to be compatible in legume-switchgrass (Panicum virgatum L.) mixtures, although there is wide variation in biomass yields and combining abilities (Springer et al, 2001) among the legume species.…”
mentioning
confidence: 99%